Recent advances in health biotechnology during pandemic - GÜNDÜZ, OĞUZHAN; ULAĞ, SONGÜL (My University, 2023)
The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which emerged in 2019, cut the epoch that will make profound fluctuates in the history of the world in social, economic, and scientific fields. Urgent needs in public health have brought with them innovative approaches, including diagnosis, prevention, and treatment. To exceed the coronavirus disease 2019 (COVID-19) pandemic, various scientific authorities in the world have procreated advances in real time polymerase chain reaction (RT-PCR) based diagnostic tests, rapid diagnostic kits, the development of vaccines for immunization, and the purposing pharmaceuticals for treatment. Diagnosis, treatment, and immunization approaches put forward by scientific communities are cross-fed from the accrued knowledge of multidisciplinary sciences in health biotechnology. So much so that the pandemic, urgently prioritized in the world, is not only viral infections but also has been the pulsion in the development of novel approaches in many fields such as diagnosis, treatment, translational medicine, virology, microbiology, immunology, functional nano- and bio-materials, bioinformatics, molecular biology, genetics, tissue engineering, biomedical devices, and artificial intelligence technologies. In this review, the effects of the COVID-19 pandemic on the development of various scientific areas of health biotechnology are discussed.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; ENERJİ VE YAKITLAR; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; ENERGY & FUELS; MATERIALS SCIENCE, COMPOSITES; Hesaplamalı Mekanik; Fizik Bilimleri; Mühendislik (çeşitli); Enerji (çeşitli); Malzemelerin mekaniği; Computational Mechanics; Physical Sciences; Engineering (miscellaneous); Energy (miscellaneous); Mechanics of Materials; COVID-19 Pandemic; health biotechnology; SARS-CoV-2; COVID-19 Pandemic; health biotechnology; SARS-CoV-2